Video reflection: An emerging tool for training client‐centred communication skills in staff supporting adults with learning disabilities in an education setting. (10th January 2020) - Meadows, Ben; Taylor, Megan; Rayment, Tara; Johnson, Jane; Mahon, Merle
Accessible summary: Video reflection is one of the best ways to help staff develop their communication skills provided the training setting is supportive. Good communication skills are important so staff can support people with learning disabilities access education. This study filmed education staff working with people with a learning disability at college. The staff watched the video so they could see themselves and think about what they did well and what they could improve on. The results found that staff were better at communicating and more confident using their communication skills after watching the video. Abstract: Background: Speech and language therapists (SLTs) contribute to communication with adults with learning disabilities by providing training to the networks that support them. The requirements for successful communication with this population are frequently complex and necessitate an effective training medium to transfer the target knowledge and skills. Video has increasingly been used as a tool to facilitate self‐reflection and behaviour change. Currently, there is limited research into the effectiveness of video‐based training in education settings for adults with learning disabilities. Therefore, this study investigated the effectiveness of video reflection training (VRT) for support staff in a college for adults with learning disabilities. Materials and Method: Ten staff members with diverse skill sets completed three VRT sessions aimed at improving their use of communication strategies. Training evaluation measures were taken before and after VRT and included use of communication strategies, self‐efficacy, training pre‐conceptions and training experience. Results: Overall, the majority of staff made gains either in their use of communication strategies or in their self‐efficacy ratings. Yet, study limitations restrict conclusions regarding whether VRT itself caused these outcomes. Interpretation revealed five factors relating to the effectiveness of VRT: tailoring training to staff's pre‐existing skills, practising facilitation techniques, providing acceptable training, increasing self‐reflection skills and using video as a reflection tool. Conclusions: Regardless of the limitations, this study provides findings that VRT is a useful tool for training support staff to use client‐centred communication skills in an education setting. Future training programmes should be individualised and tailored to staff depending on their skill sets.